EndoConf: real-time video consultation during endoscopy; telemedicine in endoscopy at its best - Deding, Ulrik; Høgh, Anders; Buch, Niels; Koulaouzidis, Anastasios; Baatrup, Gunnar; Bjørsum-Meyer, Thomas (Endoscopy International Open, 2021)
Background and study aims The aim of this study was to introduce EndoConf, a reliable and easy-to-use tool capable of optimizing clinical care in endoscopy by reducing the number of repeat endoscopy procedures, providing continuous on-the-job clinical education, and allowing a smooth transition to the next level of artificial intelligence-supported systems.Patients and methods We prospectively developed and improved a real-time conference system (EndoConf). EndoConf enables endoscopists to contact on-demand and in real time experienced endoscopists across other sites. After the initial introduction period, we registered all EndoConf-assisted procedures from our unit (Surgical Department of Odense University Hospital) over a 3-month period (Autumn of 2019).Results Of 84 EndoConf-supported procedures, 58 were eligible for further analysis. Eventually, 38 calls were made, of which only four were technically of low quality (10.5 %) while three were not answered (7.9 %). Of the 35 (92.1 %) completed EndoConf calls; 24 were referred for endoscopic mucosal resection, six were referred for transanal microsurgery preceded by transrectal ultrasonography and three were referred for multidisciplinary conference, whereas in two cases, the lesion was resected during EndoConf.Conclusions We found the EndoConf system to provide support that could reduce the number of unnecessary repeat endoscopic procedures while at the same time ensuring avoidance of any hazardous attempt at polypectomy.